A comparative assessment of the effectiveness of antibacterial treatment of the root canal with an erbium-chromium laser and a 3% solution of sodium hypochlorite with ultrasound treatment in chronic apical periodontitis - A. Yu. Rozenbaum; V. P. Tlustenko; M. A. Postnikov (Эндодонтия Today)
One of the most common complications of caries is chronic apical periodontitis. The microbial factor plays a leading role in the development of this pathological process. Consequently, the main task of endodontic treatment of chronic apical periodontitis is the qualitative antibacterial treatment of the root canal. At present, the use of ultrasound and laser is a promising direction for disinfection of root canals. With the help of a microbiological study of the microflora of the root canals of the teeth, a comparative evaluation of the antimicrobial effect of ultrasound and erbium-chromium laser was carried out before and after antibacterial treatment.